Functional outcomes of arthroscopic rotator cuff repair: transosseous technique versus single-row with anchors - Kronthal, Julio Solis; Esperón Hernández, Ramon; Martínez Escalante, Felipe; Bobadilla Lezcano, Guillermo; Cámara Arrigunaga, Felipe (International Journal of Research in Orthopaedics, 2025)
Background: Transosseous repair (TO) has declined in popularity since the introduction of suture anchors and arthroscopic methods in 1985. Nevertheless, failure rates remain significant, at 12% to 40% and the cost of these devices is considerable. Consequently, interest has revived in arthroscopic transosseous technique, the aim of this study was to evaluate whether anchorless transosseous arthroscopic fixation achieves similar or better functional outcomes than single-row fixation with anchors in patients with rotator cuff tears. Methods: 60 shoulders with complete rotator cuff tears were evaluated, divided into two groups based on fixation technique: Group 1 (transosseous) and Group 2 (single row with anchors). All patients had a minimum 12-month follow-up, including clinical assessments (VAS, range of motion) and functional questionnaires (ASES, Constant scores). Results: No significant differences were found in VAS scores at 6 months (t=0.244, p=0.404) and 12 months (t=0.220, p=0.413). Additionally, there was no superiority of either group in motion ranges at 12 months (forward flexion t=0.732, p=0.234; external rotation t=1.608, p=0.057; abduction t=0.583, p=0.281). Both groups reported high postoperative satisfaction, with no differences in ASES (t=0.153, p=0.439) and constant scores (t=0.572, p=0.285) at 12 months. Conclusions: The transosseous repair technique is as effective as single-row anchor repair for rotator cuff repair, achieving similar clinical and functional outcomes.